2020
DOI: 10.1177/0961000620907958
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration clusters, interdisciplinarity, scope and subject classification of library and information science research from Africa: An analysis of Web of Science publications from 1996 to 2015

Abstract: This study investigated the trends in the scope and subject classifications of library and information science research from authors that are affiliated with institutions in Africa. Library and information science journal articles and conference proceedings from the 54 African countries that were published between 2006 and 2015 and indexed in the Web of Science were retrieved for the study. After the removal of non-relevant articles and articles that were not available online, the library and information scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The indicator is widely used throughout the world. In Africa, there have been few bibliometric or scientometric studies on research collaboration specific to such countries as Nigeria (Fari and Ocholla, 2015), Ghana (Owusu-Nimo and Boshoff, 2017) and South Africa (Sooryamoorthy, 2013;Sooryamoorthy, 2015;Sooryamoorthy, 2017) and/or in specific disciplines or research areas such as HIV/AIDS (Onyancha, 2009), ecology (Yevide et al, 2016), engineering (Sooryamoorthy, 2011), cardiovascular research (Ettarh, 2016, natural and applied sciences (Jacobs, 2008) and library and information science (Asubiaro and Badmus, 2020;Maluleka and Onyancha, 2016;Onyancha, 2018). Bibliometric studies on research collaboration covering Africa or large geopolitical regions on the continent are rare.…”
Section: Introductionmentioning
confidence: 99%
“…The indicator is widely used throughout the world. In Africa, there have been few bibliometric or scientometric studies on research collaboration specific to such countries as Nigeria (Fari and Ocholla, 2015), Ghana (Owusu-Nimo and Boshoff, 2017) and South Africa (Sooryamoorthy, 2013;Sooryamoorthy, 2015;Sooryamoorthy, 2017) and/or in specific disciplines or research areas such as HIV/AIDS (Onyancha, 2009), ecology (Yevide et al, 2016), engineering (Sooryamoorthy, 2011), cardiovascular research (Ettarh, 2016, natural and applied sciences (Jacobs, 2008) and library and information science (Asubiaro and Badmus, 2020;Maluleka and Onyancha, 2016;Onyancha, 2018). Bibliometric studies on research collaboration covering Africa or large geopolitical regions on the continent are rare.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, studies have revealed that researchers in Africa mostly participate in international collaboration as fringe participants, not as the first authors or principal investigators (Hedt-Gauthier et al, 2019;Owusu-Nimo & Boshoff, 2017). Another study revealed that Sub-Saharan African countries collaborated more with the countries that colonized them (T. V. Asubiaro & Badmus, 2020;Boshoff, 2009). Countries that were colonized by England were more likely to collaborate with England and English-speaking countries and same for countries that were colonized by Portugal and France.…”
Section: Research Context and Motivationmentioning
confidence: 99%
“…For instance, while Zimbabwe, and Kenya are also English-speaking countries, Cameroun, Congo, and Senegal are not. Earlier studies have identified language as a determinant for collaboration between African countries(Asubiaro & Badmus, 2020). Similarly, while Zimbabwe is close to South Africa geographically, Cameroun and Sudan are not.…”
mentioning
confidence: 95%
“…We extracted data from the Web of Science the same way as described by Asubiaro and Badmus 9 for African countries for a single research area; however, our work encompassed not one research area but several, namely preclinical, clinical, and health sciences within the larger domain of biomedical sciences, and we looked for the total number of publications and the world's top 1% most cited publications each year for the decade 2008-2017.…”
Section: Databasementioning
confidence: 99%